THE APPLICATION OF THE GROUP DISCUSSION METHOD TO IMPROVE LEARNING OUTCOMES OF CHRISTIAN RELIGION AND CHARACTERISTICS MAIN MATTER THE IMPACT OF SIN FOR CLASS V STATE SCHOOL STUDENTS 066044 MEDAN ODD SEMESTERS, 2021/2022 ACADEMIC YEAR 2021/2022 - Risda Sitohang (Sean Institute, 2022)
Application of the Group Discussion Method to Improve Learning Outcomes of Christian Religion and Character Education Main Materials on the Impact of Sin for Grade V Students at SD Negeri 066044 Medan Odd Semesters for the 2021/2022 Academic YearObjectiveThis research was carried out to improve student learning outcomes in Grade V. SD Negeri 066044 Medan in the 2021/2022 academic year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are students of class V. SD Negeri 066044 Medan as many as 14 people, the instrument used to obtain data is by using a test, observing the range of values for the test is The highest and lowest values. The instrument used for data processing is to calculate the number of students' scores that have not reached the KKM and the scores that have reached the KKM. The KKM has been set at 70. The results of this study indicate that there is an increase in learning outcomes using the Character-Based Example Method with the results in Cycle 1 There are 6 students (42%) who pay close attention to the teacher's explanation. There are 7 students (50%) who actively ask questions during learning. take place. In an active discussion, there were 7 students (50%), there were 8 students who actively answered questions (60%), students who dared to do assignments on the blackboard were 7 students (50%), students who There are 8 students actively doing homework (60%), at the end of the lesson getting test results that get a score of 70 there are 5 other students (36%) less than 70. In Cycle 2 there are 12 students (90%) who pay attention to the teacher's explanation in earnest. There were 11 students (70%) who actively asked questions during the learning process. In active discussions there were 8 students (60%), 11 students actively answering questions (80%), students who dared to do assignments on the blackboard were 11 students (80%), active students doing homework there are 12 students (90%), At the end of the lesson get test results that get a score above 70 there are 12 students (86%) students who are less than 70 there are 2 students (14%), There is an increase in the number of students Completed Achieve the KKM (70), where in Cycle 1 the number of students who completed only 5 people (36%), increased to 9 people (64%) in cycle II. There is a decrease in the number of students who do not complete,